Sistema de monitoramento sem fio de temperatura aplicado a doses da vacina contra covid-19 - Pinto, Jones Castro (Brasil, 2021)
This work consists of developing hardware that uses sensors to monitor the temperature of doses of the vaccine against Covid – 19 during the storage process of the immunizing agents. The information obtained by the sensors were sent through LoRa technology using the LoRaWAN communication protocol, a communication system designed for projects that have a lower data transfer rate but require a range of up to 12 km in the communication link. To verify the functionality of the developed hardware, tests were carried out simulating a real vaccine conservation system following the recommendations of the National Immunization Plan. The information produced was made available through a web application server in a dashboard format to monitor immunizing agents.